Pengaruh Motivasi, Disiplin dan Budaya Organisasi Terhadap Kinerja Pelayanan Administrasi di Kelurahan Kuto Panji Kecamatan Belinyu Kabupaten Bangka: Penelitian - Diah Vitaloka; Nurcahyaningsih (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aims to analyze the influence of motivation, discipline and organizational culture on the performance of administrative services in Kuto Panji Village, Belinyu District, Bangka Regency. The urgency of this study is due to the fact that there are still various problems in administrative services, such as delays in service completion, low discipline of some apparatus, lack of optimal work motivation, and organizational culture that does not fully support responsive and quality services. So that it has an impact on the low level of public satisfaction with the administrative services provided. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to predetermined respondents and analyzed using multiple linear regression techniques to determine the influence of variables of work motivation, work discipline and organizational culture on the performance of administrative services, both partially and simultaneously. The results of the study show that work motivation, work discipline of the apparatus, and organizational culture have a positive and significant effect on the performance of administrative services. Partially, each variable contributes to improving the quality of administrative services, while simultaneously the three variables have a stronger influence on improving service performance. These findings indicate that the higher the work motivation of the apparatus, the better the level of discipline, and the stronger the service-oriented organizational culture, the better the performance of administrative services provided to the community.